A modified magnetic bottle electron spectrometer for the detection of multiply charged ions in coincidence with all correlated electrons: decay pathways to Xe3+ above xenon-4d ionization threshold. Issue 34 (19th August 2022) - Ismail, I.; Khalal, M. A.; Huttula, M.; Jänkälä, K.; Bizau, J.-M.; Cubaynes, D.; Hikosaka, Y.; Bučar, K.; Žitnik, M.; Andric, L.; Lablanquie, P.; Palaudoux, J.; et al.
Abstract : New magnet design of a magnetic bottle electron spectrometer allowing the detection of multiply charged ions in coincidence with n electrons. Electrons spectra obtained without and with filtering by coincidence with Xe n + ions. Abstract : Single-photon multiple photoionization results from electron correlations that make this process possible beyond the independent electron approximation. To study this phenomenon experimentally, the detection in coincidence of all emitted electrons is the most direct approach. It provides the relative contribution of all possible multiple ionization processes, the energy distribution between electrons that can reveal simultaneous or sequential mechanisms, and, if possible, the angular correlations between electrons. In the present work, we present a new magnet design of our magnetic bottle electron spectrometer that allows the detection of multiply charged Xe n + ions in coincidence with n electrons. This new coincidence detection allows more efficient extraction of minor channels that are otherwise masked by random coincidences. The proof of principle is provided for xenon triple ionization.